2020
DOI: 10.12688/gatesopenres.13152.1
|View full text |Cite
|
Sign up to set email alerts
|

HIV testing amid COVID-19: community efforts to reach men who have sex with men in three Kenyan counties

Abstract: In comparison to European and American countries, Kenya has been less impacted by the COVID-19 pandemic in terms of reported cases and mortalities. However, everyday life has been dramatically affected by highly restrictive government-imposed measures such as stay-at-home curfews, prohibitions on mobility across national and county boundaries, and strict policing, especially of the urban poor, which has culminated in violence. This open letter highlights the effects of these measures on how three community-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 9 publications
2
10
0
Order By: Relevance
“…A single-site, pre-exposure prophylaxis study 22 of 455 pregnant women in South Africa reported that 34% of patients missed visits before lockdown, increasing to 57% after lockdown (odds ratio 2•36, 95% CI 1•73-3•16). In keeping with our findings, two descriptive analyses from small studies in Kenya (two sites 14 and three sites 15 ) reported that 15-30% fewer HIV tests were done in April, 2020, than were done per month in January to March, 2020. 14,15 National laboratory data 23 from South Africa comparing the 2 months prelockdown with the first month of lockdown showed decreases of 33% in CD4 cell count (usually done at HIV diagnosis or ART initiation) and 22% in viral load testing (usually done for ART monitoring).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…A single-site, pre-exposure prophylaxis study 22 of 455 pregnant women in South Africa reported that 34% of patients missed visits before lockdown, increasing to 57% after lockdown (odds ratio 2•36, 95% CI 1•73-3•16). In keeping with our findings, two descriptive analyses from small studies in Kenya (two sites 14 and three sites 15 ) reported that 15-30% fewer HIV tests were done in April, 2020, than were done per month in January to March, 2020. 14,15 National laboratory data 23 from South Africa comparing the 2 months prelockdown with the first month of lockdown showed decreases of 33% in CD4 cell count (usually done at HIV diagnosis or ART initiation) and 22% in viral load testing (usually done for ART monitoring).…”
Section: Discussionsupporting
confidence: 86%
“…In keeping with our findings, two descriptive analyses from small studies in Kenya (two sites 14 and three sites 15 ) reported that 15-30% fewer HIV tests were done in April, 2020, than were done per month in January to March, 2020. 14,15 National laboratory data 23 from South Africa comparing the 2 months prelockdown with the first month of lockdown showed decreases of 33% in CD4 cell count (usually done at HIV diagnosis or ART initiation) and 22% in viral load testing (usually done for ART monitoring). However, decreased HIV viral load PCR testing could reflect changes in laboratory system capacity due to increased SARS-CoV-2 PCR testing, rather than changes in patient clinic attendance and ART provision.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In some settings, there have been reported adaptations in the implementation of HIV service delivery to mitigate interruptions, including adoption of telemedicine [19, 31-36], home-based HIV testing and self-testing[37-39], home or mobile delivery of antiretrovirals[34, 35, 40], use of curbside pickup (i.e. pickup of supplies without stepping out of a vehicle) for condoms, lubricants, and medications[41], and designation of surrogates such as peers to motivate and support ongoing treatment.…”
Section: Resultsmentioning
confidence: 99%
“…[32] Access to non-medical support, including cash transfers, reimbursement for the costs associated with accessing care,[19] and housing and food supplementation support, has been key to promoting ongoing engagement in care. [29, 39] However, medical support and telemedicine strategies alone are unlikely to fully mitigate the poorer HIV outcomes observed; one study from a safety-net HIV clinic in San Francisco found that the odds of viral non-suppression were 31% higher after a shelter-in place mandate compared to before the mandate, even with telemedicine services. [14] Notably, most studies describing adaptations have been in higher-income settings, though this may be a publication bias.…”
Section: Resultsmentioning
confidence: 99%